2011
DOI: 10.1002/sia.3844
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometric vanadium oxides studied by XPS

Abstract: Recovery of vanadium oxide from steelmaking slag is of great interest for Swedish steel producers and the technique for assessing the oxidation state of vanadium is crucial in the optimization of vanadium recovery. There is a large spread in the reported values of published V2p 3/2 binding energy values for various oxidation states of vanadium. Therefore, an extensive analysis of vanadium oxide standards was performed aimed at obtaining reliable data and improved methods for the preparation of representative o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
188
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 336 publications
(219 citation statements)
references
References 12 publications
29
188
0
2
Order By: Relevance
“…Now we first attempt to apply this approach to indentify the valence of V in LiMn 1 À x V x PO 4 . From the measured XPS spectra, the experimental Δ values of our samples are all ranged from 14.1 to 14.3 eV, indicating that the oxidation states of V is þ 3 [24]. Moreover, the bind of V2p 3/2 of LiMn 1 À x V x PO 4 samples was also fitted and the binding energy is around 517.3 eV, matching with that observed in Li 3 V 2 (PO 4 ) 3 (517.2 eV) [25] and again suggesting that the oxidation state of V in our doped sample is þ 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Now we first attempt to apply this approach to indentify the valence of V in LiMn 1 À x V x PO 4 . From the measured XPS spectra, the experimental Δ values of our samples are all ranged from 14.1 to 14.3 eV, indicating that the oxidation states of V is þ 3 [24]. Moreover, the bind of V2p 3/2 of LiMn 1 À x V x PO 4 samples was also fitted and the binding energy is around 517.3 eV, matching with that observed in Li 3 V 2 (PO 4 ) 3 (517.2 eV) [25] and again suggesting that the oxidation state of V in our doped sample is þ 3.…”
Section: Resultsmentioning
confidence: 99%
“…In the previous reports [13,14], the valence of V in LiMn 1 À x V x PO 4 /C was determined to be þ 3 based on the binding energy (BE) of V2p 3/2 . Herein two methods are adopted to analyze the XPS and evaluate the oxidation state of V. According to the work of Hryha et al [24], the difference in binding energies between the O1s (VO x ) core level and the V2p 3/2 level (Δ ¼ BE(O1s) -BE (V2p 3/2 )) was better for use in determining the oxidation state of the vanadium in oxides. Now we first attempt to apply this approach to indentify the valence of V in LiMn 1 À x V x PO 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These three peaks were also observed in the composite after the hydrogen thermal treatment; nevertheless, a tiny shoulder was detected at the lower binding energy of the V 2p 3/2 peak at around 512.9 eV, which may be assigned to the vanadium metallic state V 2+ due to over-reduction. [ 37 ] In general, V 4+ was found to be the dominating oxidation state on the surface of both composites. This was not a surprise even though XRD analysis of Figure 2 e indicated that the "bulk" of the vanadium oxide particle was V 2 O 3 after hydrogen thermal processing.…”
Section: +mentioning
confidence: 97%
“…6(a). The position of these peaks was ascribed to 517.4 eV, 516.1 eV, 514.1 eV and 512.9 eV, respectively 28 and the spectra were fitted using the CasaXPS software and a Shirley function to remove the background. The vanadium valence state content of the VO 2 films shown in Fig.…”
Section: Resultsmentioning
confidence: 99%